2019
DOI: 10.1136/archdischild-2018-315887
|View full text |Cite
|
Sign up to set email alerts
|

Congenital left heart obstruction: ethnic variation in incidence and infant survival

Abstract: ObjectiveTo investigate the relationship between ethnicity and health outcomes among fetuses and infants with congenital left heart obstruction (LHO).DesignA retrospective population-based review was conducted of fetuses and infants with LHO including all terminations, stillbirths and live births from 20 weeks’ gestation in New Zealand over a 9-year period. Disease incidence and mortality were analysed by ethnicity and by disease type: hypoplastic left heart syndrome (HLHS), aortic arch obstruction (AAO), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…[2][3][4] In New Zealand, the incidence of HLHS is 0.22/1000 births-similar to that in northern Europe when maternal ethnicity is European, and lower when maternal ethnicity is Māori or Pacific. 5 Mortality from the first stage procedure to the second stage procedure was 17% 2 between 1992 and 2014, similar to that reported elsewhere. 4 6 7 Antenatal detection of HLHS provides an opportunity for prenatal counselling.…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…[2][3][4] In New Zealand, the incidence of HLHS is 0.22/1000 births-similar to that in northern Europe when maternal ethnicity is European, and lower when maternal ethnicity is Māori or Pacific. 5 Mortality from the first stage procedure to the second stage procedure was 17% 2 between 1992 and 2014, similar to that reported elsewhere. 4 6 7 Antenatal detection of HLHS provides an opportunity for prenatal counselling.…”
Section: Introductionsupporting
confidence: 88%
“…There may also be differences in parental values and religious beliefs across ethnic groups. 5 23 In one study maternal education explained a large percentage of the difference in outcome seen between ethnic groups in infants with HLHS. 23 The NZ deprivation index combines a number of social and economic variables that are likely to impact access to healthcare and other resources.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…11 In a recent national population-based study from New Zealand, Cloete et al reported 56% survival to 1 year of age in hypoplastic left heart syndrome with intention to treat. 12 The improved survival between the early and late birth period was mainly explained by improved survival between stages I and II. Improved survival over time was frequently reported in the early era of Norwood surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A large SR-MA by Paradies et al has suggested that racial discrimination is a significant determinant of physical and mental health outcomes in the United States ( 80 ). While most of the studies in this review are from the United States, this finding is likely to be true in other societies, as is suggested from studies included in our review from countries such as Panama ( 24 ) and New Zealand ( 27 ).…”
Section: Discussionmentioning
confidence: 84%